Effectiveness of different dosages of vitamin E on the maturation of freshwater lobster (Cherax quadricarinatus) - Ladio, Mika; Komariyah, Siti; Putriningtias, Andika (Acta Aquatica: Aquatic Sciences Journal, 2023)
This study aims to determine the effectiveness of different doses of vitamin E on the maturation of freshwater crayfish (Cherax quadricarinatus). The method used was a Randomized Block Design (RAK) with 4 treatments and 3 replications. The treatments in this study were P1 (control), P2 (vitamin E 150 mg/kg feed), P3 (vitamin E 300 mg/kg feed), and P4 (vitamin E 450 mg/kg feed). Parameters observed in this study were Gonad Maturity Index (GIC), fecundity, and egg diameter. The results of Duncan's analysis showed that the increasing vitamin E to feed was significantly different (P<0.05) with treatment without increasing vitamin E to LAT maturation such as gonadal maturity index, fecundity, and egg diameter. However, administering different doses of vitamin E (150 mg/kg of feed, 300 mg/kg of feed, and 450 mg/kg of feed) had no significant effect on LAT maturation. The treatment without the increasing vitamin E did not show maturity, which was indicated by the value of all parameters 0, while the treatment with the increasing vitamin E to the feed resulted in a range of IKG values, fecundity, and egg diameter respectively was 8.28 - 9.84%, 230.66 - 30.66 eggs and 0.46 - 0.48 mm. The best treatment in this study was treatment with a dose of vitamin E 450 mg/kg feed because it had the highest reproductive performance and could accelerate gonadal maturity in LAT.Keywords: Egg Diameter; Fecundity; Freshwater Lobster; Maturation; Vitamin E